Thiết kế bài học STEM trong dạy học nội dung “Ánh sáng” môn Khoa học lớp 4 theo quy trình thiết kế kĩ thuật - Nguyễn, Thị Duyên; Phạm, Việt Quỳnh (Tạp chí Giáo dục, 2025)
The topic “Light” in Grade 4 Science, under the theme “Energy”, contains practical and experiential elements that are well-suited for STEM-oriented teaching. However, many primary school teachers face challenges in designing STEM lessons due to limited experience and a lack of clear instructional models. This study aims to propose a design process for developing STEM lessons and to provide a sample lesson aligned for the topic “Light” with this approach. The study employs document analysis and curriculum content analysis methods to identify theoretical and practical foundations. The findings present a feasible sample lesson that integrates STEM elements effectively, thereby supporting teachers in improving their STEM lesson planning skills and promoting the application of STEM education in primary Science teaching.